CRUSTAL CONSTRAINTS ON THE UPLIFT MECHANISM OF THE WESTERN GHATS OF INDIA - Tiwari P.Kr.; Surve G.; Mohan G. (My University, 2006)
Over 800 receiver functions (RFs) from three broadband and five short period stations deployed in the northern segment of the Western Ghats of India, were analysed to examine the crustal constraints on the rift flank uplift mechanism of the Ghats. Estimates of Moho depths, mean shear velocities and Poisson's ratios were determined and used as constraints to model the RFs. The study reveals that the crust beneath the Ghats varies in thickness between 31 and 39 km and is neither uniformly thin nor thick as required by existing hypotheses for uplift mechanism. The Poisson's ratio is 0.26 and the mean shear velocity is 3.65 km s-1. The uncertainties in the estimates of the Moho depths and Poisson's ratios are ±2 km and ±0.01, respectively. The crust beneath the Ghats is 3-4 km thinner than that beneath the adjoining low-lying coastal plains suggesting block tectonics. Modelling the RFs using crustal constraints reveals sub-Moho low-velocity zones (LVZs) with velocity reductions of 0.5-0.65 km s-1 which are confined to shallow depths of about 50 km beneath the Ghats. The persistent relief of the Ghats may be attributed to the buoyancy forces of the possibly rift related shallow upper mantle LVZs beneath the Ghats. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: BROADBAND; CRUSTAL STRUCTURE; LOW-VELOCITY ZONE; RECEIVER FUNCTION; WESTERN GHATS